Bipolar irrigated radiofrequency ablation of resistant ventricular tachycardia with a septal intramural origin: the initial experience and a description of the method. Issue 10 (25th August 2016) - Baszko, Artur; Telec, Wojciech; Kałmucki, Piotr; Iwachów, Piotr; Kochman, Karol; Szymański, Radosław; Kłopocki, Jan; Ożegowski, Stefan; Szyszka, Andrzej; Siminiak, Tomasz
Key Clinical Message: Bipolar radiofrequency (RF) ablation is effective in treatment of ventricular tachycardia originating from thick interventricular septum. The RF generator and CARTO system can be used to precisely and safely perform ablation. Standard ablation catheter can be used with indifferent ablation electrode connected to the electrode receptacle in RF generator with custom‐made cable. Abstract : Bipolar radiofrequency (RF) ablation is effective in treatment of ventricular tachycardia originating from thick interventricular septum. The RF generator and CARTO system can be used to precisely and safely perform ablation. Standard ablation catheter can be used with indifferent ablation electrode connected to the electrode receptacle in RF generator with custom‐made cable.